Modification of properties of fresh mixture for 3D printing using cement-based mortar - Vendula Kellnerová; Tomáš David; Pavel Reiterman (Acta Polytechnica CTU Proceedings)
Portland cement is traditional binding material which is applicable for various modern technologies in these days – the 3D printing is one of them. The development of 3D printers using cement-based materials for the manufacturing of structural elements and moreover entire building is novel concept of structural engineering, which combines advanced material solution and high level of automation. This paper is focused on the study of properties of fresh mixture in order to control its consistency and regime of setting time to achieve continual process of 3D printing. The properties of fresh mortar were modified by the admixture accelerating the process of hardening and stabilizing agent. The performed experimental program showed that both applied admixtures could be used for the control of the consistency of fresh mortar to achieve optimal shape of mortar layer after its extrusion.